2008
DOI: 10.1007/s10750-008-9594-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying movement of the tropical Australian cubozoan Chironex fleckeri using acoustic telemetry

Abstract: Cubomedusae are considered to have superior swimming abilities compared to other pelagic cnidarians, yet many of the theories describing such behaviours are based on anecdotal evidence, sting records or opportunistic sightings, rather than quantitative data. Acoustic telemetry was used to document the movements of adult Chironex fleckeri medusae within both coastal and estuarine habitats. The rate at which tagged medusae moved was influenced by an interaction between time period (day or night) and habitat (coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 28 publications
4
16
0
Order By: Relevance
“…Seymour et al, 2004;Gordon & Seymour, 2008;Hays et al, 2008) on individuals found in blooms to discover their fate (Table 2). Tags can be mechanically secured in cnidarians in the bell area and peduncle, or using setting glue.…”
Section: Operational Oceanography and Exploration Techniquesmentioning
confidence: 99%
“…Seymour et al, 2004;Gordon & Seymour, 2008;Hays et al, 2008) on individuals found in blooms to discover their fate (Table 2). Tags can be mechanically secured in cnidarians in the bell area and peduncle, or using setting glue.…”
Section: Operational Oceanography and Exploration Techniquesmentioning
confidence: 99%
“…The Sr:Ca ratios of statolith edge zones of medusae caught then varied only 5.7% from the mean, suggesting a relatively consistent exposure to water among individuals. Acoustic telemetry tracking of C. fleckeri medusae showed that six out of seven medusae tagged in coastal habitats remained in coastal habitats (Gordon & Seymour, 2009); the two medusae they tagged in Wooldrum Point remained there for the duration of the tracking period (up to 38 h). Although it is possible that the medusae caught in our study travelled out of the 1.5 km sampling area along Wooldrum Point during 3 days, the tracking experiment results plus the fact that exposure of medusae to estuarine influence would require a round trip of more than 10 km, gives us confidence that the Sr:Ca ratios in the outer *2.4 growth increments of statoliths from this time reflected the salinity measured at Wooldrum Point.…”
Section: Discussionmentioning
confidence: 98%
“…Adult medusae tracked with acoustic telemetry within coastal and estuarine habitats showed variable movements over short periods of time (Gordon & Seymour, 2009). Of twelve large medusae tagged, eleven remained in their respective coastal or estuarine habitats, while only one individual (IPD = 180 mm) travelled *10 km over 26 h up and down a beachfront and in and out of an estuary (Gordon & Seymour, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their low species diversity (40-50 species, Bentlage et al, 2010), they are morphologically diverse and have fast growth rates (Gordon et al, 2004), interesting life histories (Hartwick, 1991a;Straehler-Pohl & Jarms, 2005), strong swimming abilities (Gordon & Seymour, 2009), complex eyes that are used to hunt (Coates & Theobald, 2003;Nilsson et al, 2005), and powerful venom (e.g., Kintner et al, 2005). The nematocysts of ''Stingers'' (Chironex fleckeri Southcott) cause life threatening stings and have been responsible for many deaths in Australia alone (Gershwin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%